The Power of Reachability Testing for Timed Automata - Aceto, Luca; Bouyer, Patricia; Burgueno, Augusto; Larsen, Kim G. (BRICS Report Series, 1998)
In this paper we provide a complete characterization of the class of properties of (networks of) timed automata for which model checking can be reduced to reachability checking in the context of testing automata.